AN IMPLICATION STUDY OF SOCIAL MEDIA LITERACY AT SCHOOL - Meliana Zhong (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
Internet has become a familiar instrument for the school aged children in Indonesia. The use of social media platforms has changed the way of communication. In recent years, many students are drawn to social networking sites. This trend has caused the increasing reports of cyberbullying and potential cyber threats. The study took a qualitative approach and used the perimeter of the focus group discussion among 9-12 years old children in an international school in Jakarta. The thematic analysis grounded from observations, interviews and document reviews. The objective of the study is to seek the implication for schools to stand for a policy to promote constructive and safe school environment through social media literacy. It will deal with the aspects to empower students to understand that filtering and evaluating information are fundamental in daily internet browsing as well as understanding about cyberbullying and its consequences. The study concluded an implication towards the needs for schools to have a guideline for social media using among students. The guideline may serve as social media literacy to be implemented along with the digital literacy taught at schools, in expectance that students may become the responsible and ethical users of social media and technology.